Rekonstruksi Lahan Pertanian Dan Pengelolaan Sampah Efektif Di Padukuhan Warungboto, Umbulharjo - Harun, Muhammad Sandy; Ramadhan, Prima; Nafis, Zhafran; Rosadi, Adi; Akbar, Rangga Septanugera; Rahayu, Risa Dwi; Ningsih, Fajri Resti; Rahayu, Ervany Tri; Hernanda, Belvana Yasashi; Subyakto, Devayana Almira Yuliarsih; Ismail, Nawari (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The main problem faced by the community in the location is agricultural land that is less productive due to minimal maintenance and lack of effective waste management. This causes empty land to not be utilized properly and increases the amount of waste that is not managed optimally. The purpose of this activity is to improve the quality of agricultural land through land reconstruction and reuse of empty land to plant productive crops. In addition, this program also aims to provide education to the community about more effective waste management through the waste bank system. The methods used in this activity include socialization, community service, and community assistance in utilizing land and managing waste properly. The results of this activity show an increase in community participation in utilizing empty land, which is now used to plant vegetables such as chilies, tomatoes, eggplants, bakso mustard greens, and pakcoy. In addition, the existence of a waste bank provides economic benefits to the community, where the collected inorganic waste can be recycled and sold. Public awareness in sorting organic and inorganic waste has also increased significantly. With this program, it is hoped that a greener and cleaner environment will be created and there will be an increase in the economic welfare of the community. The sustainability of this program is also a major focus so that the benefits that have been obtained can continue to be felt by the local community in the long term